PENDIDIKAN JASMANI DAN PRESTASI AKADEMIK: TINJAUAN NEUROSAINS - Rachmah Laksmi Ambardini (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2009)
Physical education class is only 2 hours per week. Physical inactivity is a leading contributor to obesity and chronic disease. Numerous studies have shown positive relationships between academic achievement and physical activity. The mechanisms by which students may improve academic achievement as a result of increased physical activity through physical education included improved attention, mood, motivation, cognitive function, and neuroplasticity. Physical activity, especially aerobic activity, increased neurotransmitter activity, blood flow to the brain, and production BDNF (brain-derived neurotrphic factor). BDNF is responsible for neurons creation, survival, and resistance to damage and stress, which is support learning. Kata kunci: pendidikan jasmani, prestasi akademik, fungsi otak